Conflicts of interest challenges and solutions in business, law, medicine, and public policy - Moore, Don A. 1970- (Cambridge University Press, 2005)
This collection explores the subject of conflicts of interest. It investigates how to manage conflicts of interest, how they can affect well-meaning professionals, and how they can limit the effectiveness of corporate boards, undermine professional ethics, and corrupt expert opinion. Legal and policy responses are considered, some of which (e.g. disclosure) are shown to backfire and even fail. The results offer a sobering prognosis for professional ethics and for anyone who relies on professionals who have conflicts of interest. The contributors are leading authorities on the subject in the fields of law, medicine, management, public policy, and psychology. The nuances of the problems posed by conflicts of interest will be highlighted for readers in an effort to demonstrate the many ways that structuring incentives can affect decision making and organizations' financial well-being
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Business ethics; Legal ethics; Medical ethics; Professional ethics; Conflict of interests; Interessenkonflikt; Medizinische Ethik; Rechtsethik; Wirtschaftsethik; Aufsatzsammlung